KETERKAITAN DAN DAMPAK KARAKTERISTIK SOSIAL PETANI TERHADAP PRODUKSI PADI DI KABUPATEN ACEH UTARA - Zuriani Zuriani (LPPM Universitas Malikussaleh – Indonesia, 2017)
This research is motivated by the farmers who are generally less educated and have amindset that is difficult to be invited to change. The aim of the study was to analyze theimpact of the social characteristics of farmers on rice production in North Aceh district.The data used is a cross section taken in February 2012 based on the growing season in2011. The method used is multiple linear regression analysis. The results showed thatsocial characteristics turns rice farmers consisting of age, education, number ofdependents and simultaneously farming experience no significant effect on riceproduction in the district of Sawang. While partially, age and farming experiencesignificant effect on the level of confidence of 10% of the rice production.